Band Indie: Bentuk Gerakan Sosial Berbasis Lingkungan di Denpasar - Cahyani, Putu Kartika; Ranteallo, Ikma Citra; Hadi Tamim, Imron (JURNAL ILMIAH SOSIOLOGI (SOROT), 2014)
ABSTRACT The word Indie is derived from the word "independent". Indie Bands are bands that perform all activities related to music independently. Indie bands belong to minor labels, it means they have independency in distributing their albums. The aims of this research are to determine the factors related to perform social movements by Indie bands and to determine the forms of social movements. This research focuses on three Indie bands, which are Navicula, Dialog Dini Hari, and Nosstress. The theory that is used in this research is simbolic interaction through music by Mead, a conceptor in simbolic interactionism theory. Those Indie bands’ activities affect the community to raise their awareness to protect and keep the sustainability of their environment indirectly Keywords: Indie Band, Social Movement, Environment